Probability distribution of distance between pairs of nearest stations in wireless network - Kostin, A. (Inst Engineering Technology-Iet, 2010)
For a square area of an arbitrary size, populated by a given number of WLAN stations, uniformly distributed in the area, the exact probability distribution of distance between pairs of the nearest stations is derived. The derived probability distribution is compared with the Rayleigh probability law that describes the distance between points in an infinite Poisson point field.